The impacts of global petroleum politics and disputes on Nigeria's oil and gas industry towards Nigeria's economy - Musa, Basiru (2018)
Global petroleum politics and disputes have profound impacts on Nigeria, its citizens and economy as well as onto Nigeria as being a member of the Organisation of the Petroleum Exporting Countries (OPEC). This research focuses on analysing the effects of global petroleum politics and disputes on Nigeria's oil and gas industry and thereafter suggest effective measures that Nigeria could take to minimise them. The main questions asked by this study include, what are the effects of global petroleum politics and disputes on Nigeria's oil and gas industry? Why Nigeria is vulnerable to global oil dynamics? How could Nigeria minimise the impacts of global petroleum politics, dynamics and price crisis? These questions are posted to answer the research objectives, which include, analysing the impacts of global petroleum politics and disputes on Nigeria's oil and gas industry; examining the vulnerability of Nigeria to global oil dynamics and finding out the most cost-effective measures to minimise the effects of global petroleum politics, dynamics and price crisis. The research adopted System Theory by Anatol Rapoport as its major theory, while Conflict Triangle Theory by Johan Galtung as its supporting theory. The research employed qualitative method, using both primary and secondary data. The primary data were obtained through purposive sampling and semi-structured interview from thirty five respondents, while secondary data were obtained from relevant books, journal and e-joumal articles, The secondary data were used to strengthen and verify the findings derived from the interviews. The data were thematically analyzed. The research found that the impacts resulted into a devastating economic recession, loss of foreign direct investments, reduced oil production, destruction of social life and weakened Nigerian state. It also found that Nigeria is vulnerable to global oil dynamics because of its overdependence on oil. The study also found that, the most effective measures to overcome this vulnerability is to diversify the Nigerian economy from oil to agriculture and solid minerals. Another measure is the passage of the petroleum industry bill into law.